Soil sodicity originating from marginal groundwater - van de Craats, D. (2020)
The complex interplay between soil chemistry, soil physics, soil mechanics (as far as swell–shrink behavior is concerned), and fluctuating atmospheric conditions results in a remarkably regular relation between depth, location, and severity of a sodic layer that forms within the soil as a function of rainfall intensity. A threshold behavior is observed: sodic layer formation is absent at rainfall intensities below this threshold, whereas sodic layer thickness and hydraulic conductivity reduction increase rapidly with intensities exceeding this threshold. This is the case even for different soil types and groundwater depths. Field observations agree with our simulations: the properties of the layer with sodicity‐induced structure degradation are more strongly developed, as this layer is situated at a shallower depth. The implementation of hydraulic conductivity reduction as a function of exchangeable Na percentage and ionic strength in HYDRUS‐1D can be improved towards a smooth reduction function, changing soil physical parameters due to swelling and dispersion of clay and reconsideration of the reversibility of sodicity development.